Challenging Cultural Conventions : Qualitative Evidence from Jeevika - Sanyal, P.; Rao, V.; Majumdar, S. (World Bank, Washington, DC, 2019)
In 2006, when the Bihar Rural Livelihoods Project was launched, the state’s rural poverty ratio was 44.6 percent - 36 million of the total 82 million people in Bihar were living in poverty. Bihar is India’s third most populous state with 8 percent of the total population but ranks lowest on the human development index (HDI). Rural communities in the state are often beset by pervasive social inequalities and caste and gender hierarchies. Simultaneously, Bihar has also had a long history of progressive movements that constantly challenged upper caste hegemony. However, these movements have had limited success in address gender inequality - Bihar ranked lowest on the Gender Equality Index with lower caste women facing double subordination. Overall, rural Bihar was characterized by weak service delivery, complex political and social dynamics, limited inclusion of the poor into institutions, few economic opportunities, and a frail development infrastructure. It was in the midst of this that JEEViKA was piloted and implemented.